Tumor necrosis factor prevents Candida albicans biofilm formation - Francisco Airton Castro Rocha (Nature Portfolio, 2017)
Abstract Candida species are commensals but some develop biofilms in prosthetic materials and host surfaces that may represent up to 30% of deaths related to infections, particularly in immunosuppressed patients. Tumor necrosis factor (TNF) exhibits a plethora of functions in host defense mechanisms whereas excessive release of TNF in inflammation promotes tissue damage. Cytokines released in an inflammatory milieu may influence the development of microorganisms either by promoting their growth or displaying antimicrobial activity. In protozoa, TNF may affect growth by coupling through a lectin-like domain, distinct from TNF receptors. TNF was also shown to interact with bacteria via a mechanism that does not involve classical TNF receptors. Using an in vitro C. albicans biofilm model, we show that TNF dose-dependently prevents biofilm development that is blocked by incubating TNF with N,N’-diacetylchitobiose, a major carbohydrate component of C. albicans cell wall. This finding represents a relevant and hitherto unknown mechanism that adds to the understanding of why TNF blockade is associated with opportunistic C. albicans infections.